PERAN INDUSTRI DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Animatul Hayat, Nisa; Roisiyatin, Roisiyatin; Mulya Tirmizi, Muhammad (An Nuqud Journal of Islamic Economics, 2025)
Background of this research is about the industry, which is very important in today's era so that society can improve their well-being to meet their daily needs. From this background, the researcher focuses on the issue of underprivileged communities, specifically in Grimulya Village. The purpose of this research is to determine the role of Po Dua Elang Makmur Industry in Grimulya Village in improving the welfare of the community. The research method used a qualitative approach with a qualitative descriptive method. This study aims to describe and explain a situation that is currently happening based on facts and information obtained from the field, then analyzed based on variables, with the data source being the employees of Po Dua Elang Makmur. Data collection techniques include observation, interviews, and documentation. The results of the study show that the presence of Po Dua Elang Makmur has brought many positive impacts to the community. The conclusion of this research indicates that the role of Po Dua Elang Makmur Industry is very important in improving the welfare of the community in Grimulya Village